Ocean energy governance challenges for wave and tidal stream technologies - Wright, Glen; Kerr, S. A.; Johnson, Kate (Earthscan oceans, 2018)
Energy from wave and tidal power is a key component of current policies for renewable sources of energy. This book provides the first comprehensive exploration of legal, economic, and social issues related to the emerging ocean energy industry, in particular wave and tidal energy technologies. While offshore wind energy, sited in the oceans but not strictly derived from the ocean, is not the primary focus of the book, there is also discussion of the similarities and differences between offshore wind and wave and tidal power policy dimensions.